Abdominal Computed Tomography Angiography at 80kV: feasibility study - Maffei, Erica; Arcadi, Teresa; La Grutta, Ludovico; Midiri, Massimo; Tedeschi, Carlo; Guaricci, Andrea; Martini, Chiara; Mantini, Cesare; Cademartiri, Filippo (Acta Biomedica Atenei Parmensis, 2015)
Purpose: preliminary evaluation of different dose reduction algorithms in abdominal Computed Tomography Angiography (CTA) with standard scan protocols at 120kV vs. 80kV.Materials and Methods: prospective, randomized, crossover study. 60 consecutive patients who underwent CTA of the abdomen (Sensation 64, Siemens; Iomeprol 400 mgl/ml Bracco) for suspected or diagnosed Abdominal Aortic Aneurysm (AAA) were enrolled in the study. A standard 120kV/200mAs scan protocol was acquired in all patients (reference tube current modulated with Automatic Exposure Control). In each patient a second scan with 80kV/300mAs (Group 1; n. 20), 80kV/400mAs (Group 2; n. 20), 80kV/500mAs (Group 3; n. 20) was acquired. We used the same scan/reconstruction parameters with the same amount and kind of contrast medium. The radiation dose, the aortic attenuation values, the noise and the signal/noise ratio (S/N) were evaluated.Results: the mean dose was 9.7±2.7mSv for 120kV (all patients), 3.6±0.8mSv in Group1 (80kV), 5.0±0.6mSv in Group 2 (80kV) and 5.9±1.2mSv in Group 3 (80kV), respectively. The aortic attenuation was 350±59HU (120kV) vs. 534±100HU (80kV), 12±3.5 (120kV) vs. 8.8±3.6 (80kV) for the whole population. Aortic attenuation and S/N were: 328±40HU (120kV) vs. 494±61HU (80kV), 11±2 (120kV) vs. 7±2 (80kV) in Group1; 353±77HU (120kV) vs. 551±117HU (80kV), 11±2.8HU (120kV) vs. 8.4±2.6 (80kV) in Group 2; 389±55HU (120kV) vs. 598±117HU (80kV), 15±5 (120kV) vs. 12±5 (80kV) in Group 3, respectively (p